The Impact of TikTok Advertising on Purchase Intention in the F&B Industry: The Mediating Role of Brand Awareness - Haslindar Ibrahim; Rudresh Pandey; Rusydina Amirah Mohd Riduan; Saw Jia Hui; Sarah Qamarina Meor Ahmad Fadzil; Sally Poh Jia Yi; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study investigates the impact of TikTok advertising on brand awareness and purchase intention within the Food and Beverage (FB) industry. With the rapid growth of short-form video content, TikTok has become an excellent platform where businesses can engage with their consumers and effectively promote their brands. Nonetheless, there is limited academic evidence on how TikTok advertising influences consumer behaviour in the FB context. This research adopted a quantitative research design in which data were gathered via an online survey from a sample of 150 active TikTok users who had been exposed to advertisements in the FB industry. Using multiple regression analysis, the data were analysed to test the relationships between TikTok advertising, brand awareness and purchase intention. The findings reveal that TikTok advertising has significantly enhanced both brand awareness and purchase intention, with brand awareness partially mediating this relationship. This study shows the potentiality of TikTok as a digital marketing tool in improving brand presence and driving consumer purchasing behaviour. Thus, the results have important implications for marketers in developing engaging and creative TikTok content strategies to increase consumer engagement and sales in the FB sector.